Assessment of silica content in groundwater of Peninsular Indian region using statistical techniques - Kishan Singh Rawat; Sudhir Kumar Singh; Vinod Kumar Tripathi (Indonesian Journal of Geography, 2020)
The groundwater resources from open dug wells are the ultimate and inevitable drinking water source in Chennai municipality. These are of shallow depth of 8 to 10m with a static water depth range of 30 to 75 m. This study's objective was to assess silica (in the form of Silicon Dioxide, SiO2) in groundwater and to establish their baseline concentration. Twelve wells were monitored in the study area, in some parameters, namely: Chloride (Cl-), Total Dissolved Solids (TDS), pH, Electrical Conductivity (EC), and SiO2. We examined the existing relationship between silica and other measured water quality parameters (Cl-, pH, TDS, and EC) using Spearman correlation matrix analysis in SPSS software and Normalized Difference Dispersal Index (NDDI) in Simplex Numerix software that was applied to identify the hotspots of SiO2. The water pH ranges from 8.09 to 8.37 (slightly alkaline) with an appreciable amount of TDS (730.50 to 1294.50 ppm). The groundwater also contains abundant silica (15.50 to 24.0 ppm), Cl- (106 to 438 ppm), and EC (759.50 to 1837.50 µS/cm). Further, a geostatistical tool was used to derive NDDI map of groundwater quality parameters and quantified site-specific variations in parameters, namely SiO2, Cl-, pH, TDS, and EC values. Average NDDI value enrichment was exhibited by SiO2 (0.09, ≈ 0.1) it reﬂects accretion, while average NDDI values of Cl- (–0.09, ≈–0.1), EC (–0.04), TDS (–0.03), and pH (–0.02), it outlined that by dilution in particular groundwater parameter.